AN ANALYSIS OF THE THAILAND TEACHERS WAYS IN USING LASAGNA MILKSHAKES SONG TO TEACH VOCABULARY FOR YOUNG LEARNERS - Eadnai, Chonlakarn (Journal of English Teaching and Linguistics Studies (JET Li), 2023)
The purpose of the study was to know the way the Thailand teachers uses Lasagna milkshakes song to teach vocabulary for young learners. This study employed descriptive qualitative design by using observation sheet and video recording as the instruments. The sample of the study was the sixth English teacher of Samakkee Islam Wittaya School. The finding of the study was that the English teacher used four ways to teach vocabulary: introducing, modelling, practicing, and applying. Therefore, the researcher concluded that the teacher used introducing, modelling, practicing, and applying the ways when she taught English by using Lasagna Milkshakes Song to students.